Finite Element Analysis for Stress Distribution in a Proton Exchange Membrane Fuel Cell Stack - Nurato,; Majlan, Edy Herianto; Wan Daud, Wan Ramli; Teuku Husaini,; Rosli, Masli Irwan; Sulong, Abu Bakar; Sebayang, Darwin (International Journal of Integrated Engineering, 2019)
The component design of a proton exchange membrane fuel cell (PEMFC) considerably affects pressure distribution in the PEMFC stack by creating uniform and effective pressure distribution. Assembly and component designs are essential in the PEMFC system to achieve optimal performance and durability of the PEMFC stack. Inadequate pressure in the stacking process can damage the cells and cause leakage and contact resistance. Moreover, an uneven distribution of pressure produces hot spots that can damage the system. Achieving the optimal design with reduced production cost requires pressure distribution simulation during the assembly. Finite element analysis (FEA) was used to analyze system behavior with pressure variation during assembly by using Autodesk Inventory software. This study discussed the geometric modeling and FEA of the tensile distribution of the PEMFC stack. The detailed components reported on the geometry, dimensions, and mechanical properties of PEMFC components, such as membranes, gas diffusion layers, end plates, and bipolar plates. Results from the simulations showed no significant difference in the deformation of cells in the PEMFC stack, with changes in tensile distribution.